Enzymatic-enhanced production of gaharu oil : effects of enzyme loading and duration time - Hong, Siau Huey (2008)
Gaharu, a resinous wood that occurs in trees is belong to Aquilaria genus. It contains more than 12 chemical components that can be extracted that produce aromatic smells. To enhance oil availability and extractability, the effect of enzyme to substrate ratio and pretreatment time were studied. There are two main processes involved: enzymatic pre-treatment to break down the cell wall of gaharu, and extraction of the gaharu oil. The gaharu woods undergo drying and grinding processes before enzymatic hydrolysis. Gaharu were enzymatically hydrolyzed using Celluclast 1.5 L and the extraction was carried out using hydro-distillation. The extracted oil were then collected and analyzed by calculating the percentage of gaharu oil yield. Prolonged pretreatment time during enzymatic pretreatment process significantly increased the extraction rate of oil from gaharu. The longest pretreatment time, 9 hours gives the yield of 0.1275%. The higher enzyme to gaharu ratio, the higher yield of extracted oil has been achieved. With the highest ratio, 8 ml enzyme/ 400 g gaharu, the yield of extracted gaharu oil is 0.08375%.